Predispositions to Lymphoma: A Practical Review for Genetic Counselors. Issue 6 (6th June 2016) - Similuk, Morgan; Rao, V. Koneti; Churpek, Jane; Lenardo, Michael
Abstract: This review provides a synopsis for genetic counselors of the major concepts of lymphoma predisposition: genomic instability, immune deficiency, inappropriate lymphoproliferation, and chronic antigen stimulation. We discuss syndromes typifying each of these mechanisms. Importantly, our review of the genetic counseling literature reveals sparse discussion of genetically‐based immune‐mediated lymphoma predisposition, which we address in depth here. We aim to increase awareness among genetic counselors and colleagues in oncology about familial susceptibility and facilitate critical thinking about lymphoma risk assessment. Clinical application of this knowledge is aided by recommendations for collection of personal and family history to guide risk assessment and testing. Lastly, we include a special discussion of genetic counseling issues including perceptions of the context, nature, and magnitude of lymphoma risk, as well as coping with awareness of susceptibility to lymphoma.